A Highly Contiguous and Annotated Genome Assembly of the Lesser Prairie-Chicken (Tympanuchus pallidicinctus). (17th March 2023) - Black, Andrew N; Bondo, Kristin J; Mularo, Andrew; Hernandez, Alvaro; Yu, Yachi; Stein, Carleigh M; Gregory, Andy; Fricke, Kent A; Prendergast, Jeff; Sullins, Dan; Haukos, David; Whitson, Michael; et al.
Abstract: The Lesser Prairie-Chicken ( Tympanuchus pallidicinctus ; LEPC) is an iconic North American prairie grouse, renowned for ornate and spectacular breeding season displays. Unfortunately, the species has disappeared across much of its historical range, with corresponding precipitous declines in contemporary population abundance, largely due to climatic and anthropogenic factors. These declines led to a 2022 US Fish and Wildlife decision to identify and list two distinct population segments (DPSs; i.e., northern and southern DPSs) as threatened or endangered under the 1973 Endangered Species Act. Herein, we describe an annotated reference genome that was generated from a LEPC sample collected from the southern DPS. We chose a representative from the southern DPS because of the potential for introgression in the northern DPS, where some populations hybridize with the Greater Prairie-Chicken ( Tympanuchus cupido ). This new LEPC reference assembly consists of 206 scaffolds, an N50 of 45 Mb, and 15, 563 predicted protein-coding genes. We demonstrate the utility of this new genome assembly by estimating genome-wide heterozygosity in a representative LEPC and in related species. Heterozygosity in a LEPC sample was 0.0024, near the middle of the range (0.0003–0.0050) of related species. Overall, this new assembly provides a valuable resource that will enhance evolutionary and conservation genetic research in prairie grouse.